1998
DOI: 10.1177/089780189801000414
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Home Health Care Services by Elderly Patients with Heart Failure

Abstract: Heart failure is one of the most common reasons for admission to home health care among older adults Patients with heart failure present complex challenges for home health care agency staff, given the chronic yet variable nature of the disease and the importance of behavioral factors in long-term management of heart failure. The purpose of this study was to examine the patterns of health service utilization and outcomes of home care among elderly home care patients with heart failure. The sample included 104 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The studies were published from 1998 to 2017 in journals that focused on home care and management, nursing, and health services research. The majority (n=5) of the included studies were observational, 27 31 of which two were descriptive in nature 27 , 28 and three used retrospective cohort designs. 29 31 One study was a quasi-experimental study with pre- and post-intervention design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were published from 1998 to 2017 in journals that focused on home care and management, nursing, and health services research. The majority (n=5) of the included studies were observational, 27 31 of which two were descriptive in nature 27 , 28 and three used retrospective cohort designs. 29 31 One study was a quasi-experimental study with pre- and post-intervention design.…”
Section: Resultsmentioning
confidence: 99%
“…One study was missing outcome data 32 and several were missing demographic and clinical information on study participants. Two studies 27 , 28 found interesting trends but did not perform statistical analyses to discern whether these trends were statistically significant. Finally, reverse causality limited the validity and generalizability of the three studies that examined the effect of HCWs on readmission rates, since they did not attempt to adjust for HF patients’ severity of disease or their caregiving needs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second contextual factor, functional status, is defined as elders' ability to perform ADLs and IADLs independently. It is usually operationalized as functional limitations and has often been shown to be the strongest predictor of use of home care services by Anglo elders (Alkema et al, 2006;McCusker et al, 2001;Moulton, McGrane, Beck, Holland, & Christopher, 1998) and Mexican American elders (Burnette & Mui, 1995;Wallace et al, 1998), with a variety of diagnoses. We expected a negative relationship between functional status and use of home care services.…”
Section: Contextual Factorsmentioning
confidence: 99%
“…Changes in the acuity of the patient population due to decreased hospital length of stay have required increased accountability in the standards of home health care. Nurses are now caring for patients with more complex medical and technological needs and are providing care in the home for patients much earlier in their disease process (Ellenbecker & Warren, 1998;Moulton, McGrand, Beck, Holland, & Christopher, 1998). As the expectations and level of care have advanced, so has the need for autonomous critical thinking and anticipatory problem solving with patient and family dynamics.…”
Section: Early Development Of the Cvspmentioning
confidence: 99%